A Prospective Study to Evaluate the Prevalence of Microsatellite Instability in Endometrial Carcinoma by using Immunohistochemistry for Mismatch Repair Proteins as a Surrogate Marker - Solanki, Prithviraj K.; Mandolkar, Mahesh; Kulkarni, Padmaj (Indian Journal of Medical and Paediatric Oncology, 2024)
Aim Use of immunohistochemistry for mismatch repair (MMR) proteins to identify the prevalence of microsatellite instability (MSI) in cases of endometrial carcinoma and its subsequent correlation with various histopathological parameters.Materials and Methods The expression of MMR proteins, viz PMS2, MLH1, MSH2, and MSH6, were assessed in 114 endometrial cancer cases by immunohistochemistry using Dako EnVision FLEX system, on paraffin blocks of tumor tissue fixed in 10% formalin.Results We studied 114 endometrial cases for MMR protein expression, of which the majority were of endometrioid histologic subtype (n = 93, 81.6%), whereas the remainder comprised serous carcinoma (n = 12, 10.5%), clear cell carcinoma (n = 1, 0.9%), carcinosarcoma (n = 5, 4.4%), and dedifferentiated uterine carcinoma (n = 3, 2.6%). Twenty-one (18%) of these cases were found to be deficient for MMR proteins, of which 20 were of endometrioid histologic subtype and only 1 was dedifferentiated uterine carcinoma. Loss of MMR protein expression occurred in pairs of either PMS2 and MLH1 or MSH2 and MSH6.Conclusion MSI is one of the major molecular pathways contributing to tumorigenesis in endometrial carcinomas. Immunohistochemistry for MMR proteins is a highly sensitive and cost-effective alternative for molecular testing for MSI. It is also a great tool for screening patients for Lynch syndrome. Immunohistochemical testing for MMR should be offered to all patients of endometrial cancers.
Keywords: mismatch repair proteins; microsatellite instability; Lynch syndrome; endometrial cancer; uterine corpus cancer